2020
DOI: 10.1785/0120190253
|View full text |Cite
|
Sign up to set email alerts
|

Within-Station Variability in Kappa: Evidence of Directionality Effects

Abstract: One of the most commonly used parameters to describe seismic attenuation is the high-frequency spectral decay parameter Kappa (κr), yet the physics behind it remain little understood. A better understanding of potential factors that lead to large scatter in estimated values of κr constitutes a critical need for ground-motion modeling and seismic hazard assessment at large. Most research efforts to date have focused on studying the site-to-site and model-to-model variability of κ, but the uncertainties in indiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 52 publications
2
6
0
Order By: Relevance
“…Although the ground response is coupled in the two horizontal directions, it is common in site response assessments to treat the two horizontal components independently. In addition, Ji et al (2020) recently observed κ values that are directionally dependent, and this finding supports our approach of not discarding κ values that are more than 20% different.…”
Section: Data Analysis Proceduressupporting
confidence: 82%
“…Although the ground response is coupled in the two horizontal directions, it is common in site response assessments to treat the two horizontal components independently. In addition, Ji et al (2020) recently observed κ values that are directionally dependent, and this finding supports our approach of not discarding κ values that are more than 20% different.…”
Section: Data Analysis Proceduressupporting
confidence: 82%
“…Some of the record-to-record variability that we find for η may be regarded as similar to the within-station variability that Ji et al (2020) and Bora et al (2017) show for κ 0 . They report that the within-station variability of κ 0 can be even larger than the variability of κ 0 between different stations.…”
Section: Variability Of ηsupporting
confidence: 81%
“…The two horizontal spectra of an earthquake are combined into a single one by taking the root-mean-square (rms). We opted to average the horizontal components to reduce the influence of the azimuthal direction on the κ, η and ζ measurements (Ji et al, 2020).…”
Section: Datamentioning
confidence: 99%
See 2 more Smart Citations